Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/mmr.2016.4761
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of farnesoid X receptor activation on metabolism in a diabetic rat model

Abstract: Farnesoid X receptor (FXR) is an important regulator of glucose and lipid homeostasis. However, the exact role of FXR in diabetes remains to be fully elucidated. The present study examined the effects of chenodeoxycholic acid (CDCA), an agonist of FXR, on metabolism profile in a rat model of type 2 diabetes mellitus (T2DM). Male Wistar rats (8‑week‑old; n=40) were randomized into the following four groups (n=10): Untreated control, CDCA‑treated, T2DM, and CDCA‑treated T2DM. To establish the T2DM model, the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Despite the scarcity of data about the role of CDCA in CNS, yet in the periphery, a 2016 study by Zhang et al [30] reported that improved insulin sensitivity was achieved through CDCA agonistic activity to FXR. In addition, CDCA was found to upregulate the expression of GLUT4, which was suggested to be mediated through FXR binding to GLUT4-FXR response element (FXRE) in the GLUT4 promoter; thus, indicating that FXR is a new transcription factor for GLUT4 and highlighting the role of FXR and its agonists in insulin sensitivity and glucose homeostasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarcity of data about the role of CDCA in CNS, yet in the periphery, a 2016 study by Zhang et al [30] reported that improved insulin sensitivity was achieved through CDCA agonistic activity to FXR. In addition, CDCA was found to upregulate the expression of GLUT4, which was suggested to be mediated through FXR binding to GLUT4-FXR response element (FXRE) in the GLUT4 promoter; thus, indicating that FXR is a new transcription factor for GLUT4 and highlighting the role of FXR and its agonists in insulin sensitivity and glucose homeostasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…FXR mRNA transcript was measured relative to the housekeeping gene, β‐actin, which was used as an internal control. Sequence‐specific primers were designed as follows (Zhang et al, ): rat FXR forward primer (5′‐GCGAAAGTGCTGGGCTTTG‐3′) and reverse primer (5′‐TGTGCTTCTGGGATGGTGGT‐3′) (GenBank Accession No. NM_021745.1); rat β‐actin forward primer (5′‐CGTTGACATCCGTAAAGACCTC‐3′) and reverse primer (5′‐TAGGAGCCAGGGCAGTAATCT‐3′) (GenBank Accession No.…”
Section: Methodsmentioning
confidence: 99%
“…CDCA functions as a FXR agonist and administration of CDCA in a rat T2DM model reduced insulin and triglyceride levels but did not reduce body weight while FXR gene expression in the liver was increased [87]. However, the other major bile acid signaling receptor, TGR5, could have also mediated this effect but this was not tested in this study [85,87]. In a mouse model, bacterial bile acid modification in the gut modulated lipid metabolism and contributed to weight gain in the host [88].…”
Section: Bile Acid Metabolismmentioning
confidence: 98%
“…Activation of the nuclear receptor FXR has been associated with beneficial effects on metabolism such as reduction of body weight and inflammatory markers in mice [86]. CDCA functions as a FXR agonist and administration of CDCA in a rat T2DM model reduced insulin and triglyceride levels but did not reduce body weight while FXR gene expression in the liver was increased [87]. However, the other major bile acid signaling receptor, TGR5, could have also mediated this effect but this was not tested in this study [85,87].…”
Section: Bile Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation